Tumor-associated macrophages contribute to cholangiocarcinoma progression and chemoresistance through activation of ID1 - Yinghao Guo; Shuangda Miao; Yun Jin; Qi Li; Yihang Wang; Xiaoxiao Zhang; Jiangtao Li (Annals of Hepatology)
Introduction and Objectives: Tumor-associated macrophages (TAM) can influence both cancer growth and chemoresistance, but the specific mechanisms involved in these processes in cholangiocarcinoma (CCA) are unclear. Materials and Methods: We explored the distribution of TAM in CCA samples by multiplex immunofluorescence staining and tested the effects of TAM on CCA in vitro and in vivo. We then investigated the mechanisms underlying these effects using the Luminex assay, RNA sequencing, western blotting, flow cytometry, and co-immunoprecipitation. Results: The infiltration of TAM was strongly increased in the cholangiocarcinoma tumor microenvironment. Oncostain M (OSM) secreted by TAM increased the proliferation and chemotherapeutic resistance of CCA cells both in vitro and in vivo. The results of transcriptome sequencing analysis, Western blot analysis, and immunofluorescence staining confirmed that OSM can promote Yap nuclear translocation and its subsequent formation of complexes with SMADs to upregulate the expression of inhibitor of DNA binding 1 (ID1). Conclusions: TAM promotes CCA progression and chemoresistance through activating OSM-Yap-ID1.